Economic Evaluation of Cooling Storage Warehouses in Hot and Dry Regions for Fruits Using Different Renewable Energies - Ali Mostafaeipour; Afsaneh Nasiri (Journal of Renewable Energy and Environment, 2020)
In hot and dry regions, air conditioning is used for many different applications like residential, industry, and agriculture and dairy products. This research studies the applicability of wind and solar energies for cooling fruit storage warehouse in the hot and dry region of Yazd in Iran. The studied case is a fruit warehouse with an area of 4240 m2 resulting in a storage capacity of about 1000 tons. For this purpose, the heat gain of the warehouse is determined, and the obtained cooling load is then used to examine the solar and wind energy to power a conventional warehouse system. Different scenarios are examined for this research such as solar air conditioner, solar absorption chiller, wind catcher, and a combination of solar air conditioners and solar absorption chiller for cooling the fruit warehouse. Comparison and economic evaluation of different scenarios show that the solar air conditioning ranks first for this purpose. Results are then validated using value engineering methodology. Solar air conditioning with the highest net present value (NPV) of 4,865,040,418 Rials and the best internal rate of return (IRR) value of 182.98 % was determined to be the best approach among the studied methods. The results of this research can be applied to other regions with similar climatic conditions too.